2011
DOI: 10.1007/s10114-011-9366-6
|View full text |Cite
|
Sign up to set email alerts
|

Product of functions in BMO and H 1 in non-homogeneous spaces

Abstract: Abstract. Under the assumption that the underlying measure is a nonnegative Radon measure which only satisfies some growth condition and may not be doubling, we define as in [BIJZ] the product of functions in the regular BM O and the atomic block H 1 in the sense of distribution, and show that this product may be split into two parts, one in L 1 and the other in some Hardy-Orlicz space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Let (X , d, µ) be an RD-space. The problem about the product of f ∈ H 1 at (X , d, µ) and g ∈ BMO(X , d, µ) was first studied by Feuto [9]. In [9], Feuto showed that the product of f ∈ H 1 at (X , d, µ) and g ∈ BMO(X , d, µ), viewed as a distribution, can be written as a sum of an integrable function and a distribution in some adapted Hardy-Orlicz space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let (X , d, µ) be an RD-space. The problem about the product of f ∈ H 1 at (X , d, µ) and g ∈ BMO(X , d, µ) was first studied by Feuto [9]. In [9], Feuto showed that the product of f ∈ H 1 at (X , d, µ) and g ∈ BMO(X , d, µ), viewed as a distribution, can be written as a sum of an integrable function and a distribution in some adapted Hardy-Orlicz space.…”
Section: Introductionmentioning
confidence: 99%
“…The problem about the product of f ∈ H 1 at (X , d, µ) and g ∈ BMO(X , d, µ) was first studied by Feuto [9]. In [9], Feuto showed that the product of f ∈ H 1 at (X , d, µ) and g ∈ BMO(X , d, µ), viewed as a distribution, can be written as a sum of an integrable function and a distribution in some adapted Hardy-Orlicz space. Recently, Ky [27] improved the above result via showing that the product g × f can be written into a sum of two linear operators and via replacing the Hardy-Orlicz space by H log (X , d, µ) which is a smaller space than the aforementioned Hardy-Orlicz space and is known to be optimal even when X = R D endowed with the D-dimensional Lebesgue measure.…”
Section: Introductionmentioning
confidence: 99%
“…Definition 2.3. The triple (, 𝑑, 𝜇) is called an RD-space, if it is a space of homogeneous type and 𝜇 satisfies the reverse doubling condition: There exist constants 𝜅 ∈ (0, ∞) and 𝐶 2 ∈ (0, 1] such that, for all 𝑥 ∈ , 0 < 𝑟 < 2 diam() and 1 ≤ 𝜆 < 2 diam()∕𝑟, Similar to [14], we will also assume that there exists a positive nondecreasing function 𝜑 defined on [0, ∞) such that for all 𝑥 ∈  and 𝑟 > 0, 𝜇(𝐵(𝑥, 𝑟)) ≈ 𝜑(𝑟).…”
Section: Spaces Of Homogeneous Type and Rd-spacesmentioning
confidence: 99%